Dampak Faktor Pemicu Terjadinya Displaced Commercial Risk Terhadap Keputusan Nasabah Untuk Tetap Menjadi Nasabah Bank Syariah Di Surabaya - Yonindya Rohmatur A.; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to know if the three factor triggers of Displaced Commercial Risk (DCR) have affect partially to the decision of costumer to remain as the costumer of sharia bank. The method used is quantitative methods through questionnaire using likert scale by multiple linear regression analysis with reliability test and validity, classic assumption test, and hypothesis test.. The sample used is 100 sharia bank’s costumer who comply the criteria sample assigned. simultaneously rate of return, bank’s operational, and profit sharing expectation significantly affect to the decision of costumer, and partially the rate of returnand bank’s operational significantly affect to the decision of costume r, but partially the expectation of profit sharing not significantly affects to the decision of costumer.